Expanding the lens of institutions: a holistic approach - Barbar, Julia (Frontiers in Political Science, 2025)
This article critically examines the reliance on the concept of institutional voids in emerging market studies within institutional research, advocating for a more nuanced and configurational understanding of institutional dynamics and complexities, particularly in the MENA region. It reviews various strands of Institutional Theory, assesses the limitations of the institutional voids concept, and underscores the need for a holistic approach to institutional research—one that is both theoretically and methodologically comprehensive. It argues for the importance of disentangling institutional concepts and ensuring that methodological approaches are contextually relevant and appropriate. The article concludes by presenting four key takeaways for developing a more comprehensive and nuanced approach to institutional research.